Glioma‐derived macrophage migration inhibitory factor (MIF) promotes mast cell recruitment in a STAT5‐dependent manner2. Issue 1 (18th September 2013) - Põlajeva, Jelena; Bergström, Tobias; Edqvist, Per-Henrik; Lundequist, Anders; Sjösten, Anna; Nilsson, Gunnar; Smits, Anja; Bergqvist, Michael; Pontén, Fredrik; Westermark, Bengt; Pejler, Gunnar; Forsberg Nilsson, Karin; et al.
Abstract : Recently, glioma research has increased its focus on the diverse types of cells present in brain tumors. We observed previously that gliomas are associated with a profound accumulation of mast cells (MCs) and here we investigate the underlying mechanism. Gliomas express a plethora of chemoattractants. First, we demonstrated pronounced migration of human MCs toward conditioned medium from cultures of glioma cell lines. Subsequent cytokine array analyses of media from cells, cultured in either serum‐containing or ‐free conditions, revealed a number of candidates which were secreted in high amounts in both cell lines. Among these, we then focused on macrophage migration inhibitory factor (MIF), which has been reported to be pro‐inflammatory and ‐tumorigenic. Infiltration of MCs was attenuated by antibodies that neutralized MIF. Moreover, a positive correlation between the number of MCs and the level of MIF in a large cohort of human glioma tissue samples was observed. Further, both glioma‐conditioned media and purified MIF promoted differential phosphorylation of a number of signaling molecules, including signal transducer and activator of transcription 5 (STAT5), in MCs. Inhibition of pSTAT5 signaling significantly attenuated the migration of MCs toward glioma cell‐conditioned medium shown to contain MIF. In addition, analysis of tissue microarrays (TMAs) of high‐grade gliomas revealed a direct correlation between the level of pSTAT5 in MCs and the level of MIF in the medium. In conclusion, these findings indicate the important influence of signaling cascades involving MIF and STAT5 on the recruitment of MCs to gliomas. Highlights: MC accumulation in glioma is malignancy grade‐dependent. Neutralization of MIF produced by glioma cells lowers the extent of MC migration. The extent of MC recruitment is correlated with the level of MIF. MIF‐induced accumulation of MCs in vivo is associated with activation of STAT5.